The Quintessence of Marketing What You Really Need to Know to Manage Your Marketing Activities - Bickhoff, Nils.; Hollensen, Svend; Opresnik, Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
What actually is marketing? Many people think of marketing as only sales and advertising because every day we are bombarded with TV commercials, flyers, catalogues, sales calls, and commercial e-mail. However, selling and advertising are only one element of marketing. Today, marketing must be understood not in the old sense of making a sale but in a contemporary and holistic sense of satisfying customer needs. In this book the authors develop the Quintessential Marketing Arena by following the logic of the three major steps of the marketing process. Along this process they present the fourteen most important marketing instruments that occur during this process. Having read this book: You will have a basic understanding of marketing and the process of marketing management You will know the most important marketing instruments and how they interact You can develop your own marketing plan based on the Quintessential Marketing Arena
Marketing and Marketing Management: A First Basic Understanding -- Step 1 - Market Analysis: Structuring and Evaluating the Market Information -- Step 2 - Strategic and Operative Marketing Planning: Segmenting, Targeting, Positioning -- Step 3 - Marketing Implementation: Executing the Marketing Plan -- Conclusion: Marketing and Railroad Companies.
Keywords: Economics; Industrial management; Marketing; Economics/Management Science; Marketing; Management/Business for Professionals